MENTAL STATE LANGUAGE DEVELOPMENT: THE LONGITUDINAL ROLES OF ATTACHMENT AND MATERNAL LANGUAGE. Issue 3 (5th May 2017) - Becker Razuri, Erin; Hiles Howard, Amanda R.; Purvis, Karyn B.; Cross, David R.
ABSTRACT: Maternal mental state language is thought to influence children's mental state language and sociocognitive understanding (e.g., theory of mind), but the mechanism is unclear. The current study examined the longitudinal development of mental state language in mother–child interactions. The methodology included assessments of the child and/or mother–child dyad at six time points between 12 to 52 months of the child's age. Measures determined child's attachment style and language abilities, and mental state language used by mother and child during a block‐building task. Results showed that (a) mental state talk, including belief and desire language, increased over time; (b) there were differences between the type of mental state words used by the mother in insecure versus secure dyads; (c) there were differences in patterns of mental state words used in both mothers and children in insecure versus secure dyads; and (d) attachment appeared to exert a consistent influence over time.